Retardation of wetting for membrane distillation by adjusting major components of seawater. (15th May 2020) - Kim, Hye-Won; Yun, Taekgeun; Hong, Seungkwan; Lee, Seockheon; Jeong, Seongpil
Abstract: Wetting by fouling is phenomenon specific to membrane distillation (MD) and are regarded as challenges to the seawater membrane distillation (SWMD) process. To understand fouling and wetting, the influence of Mg and Sr crystals, which can potentially cause scaling, as well as Ca crystals deposited on the membrane surface were investigated. Mg(OH)2 and CaSO4 had significant impact on fouling and wetting. Even if CaCO3 and SrSO4 had no effects on fouling and wetting as single salts, CaCO3 and CaSO4 were dominant in synthetic seawater without Mg(OH)2 . However, the occurrence of Mg(OH)2 scales became a cause for concern if Ca ion was removed from seawater for the prevention of fouling and wetting. Therefore, Mg as well as Ca should be removed for proper fouling and wetting control. NaOH/Na2 CO3 softening was used for the removal of Ca and Mg ions. In addition, based on the inhibition effects of Mg ions on Ca scales, a new pretreatment method involving the injection of MgCl2 to increase the Mg /Ca ratio was examined. Graphical abstract: Image 1 Highlights: Wetting in MD process using a seawater was observed by visualization system. Wetting by Mg(OH)2 occurred during the MD process was firstly suggested. Retardation of the wetting in MD process was achieved by a Mg addition to the feed. The SrCO3 scalant was formed when major components of seawater were removed. The CaCO3 and CaSO4 scalants resulted in the partial and full wettings, respectively.